Mal Verses in Al Maraghi's Exegesis; Study of People Indonesian’s Reality - Muhammad Anis Mawardi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2017)
Social changes faced by Muslims in the modern era have caused a number of serious problems relating to Islamic law. Islam aims to maintain basic human needs, namely: religion, body and soul, reason, honor (ancestry), and property. Among these five things, property is often a real problem inherent in human life. In Islam property is regulated through muamalah law and prohibits actions that can cause harm, such as theft, robbery, corruption, manipulation, smuggling, exploration of natural resources in an all-inclusive manner, including wasteful attitudes and consumerism. So that property has an important connection in social life. This is where al-Maraghi exegesis will explain the mal verses in the context of Indonesian society.